Aid And Growth : Empirical Evidence From Pacific Island Countries - Lau, Evan; Jayaraman, T.K (Universitatea SPIRU HARET, 2011)
The Pacific island countries (PICs) have been among the world’s top ten recipients of official development assistance (ODA) on a per capita basis. This paper seeks to examine the effectiveness of external aid by undertaking a panel data study covering five countries in the South Pacific, namely Fiji, Samoa, Solomon Islands, Tonga and Vanuatu utilizing the annual data over a twenty-five year period.